Consumer Behaviour in the Food Supplement Market - Štorková, Viktorie (2024)
The bachelor thesis “Consumer Behaviour in the Food Supplement Market” aims to identify the factors influencing consumer buying behaviour, analyse the decision-making process consumers undergo and assess the role of advertising in buying processes to provide recommendations for marketers in the pharmaceutical industry. The first part of the thesis includes a literature review explaining the food supplement market and consumer behaviour, while the second part consists of the described methodology used for research and the research findings and recommendations. The key findings include factors influencing consumer behaviour, identification of three consumer groups with different behavioural patterns, and the role of advertisement in purchasing decisions. The thesis is intended for pharmaceutical marketers, businesses, and individuals active in the food supplement market.